Estudo da fauna flebotomínea (Diptera: Psychodidae) na localidade de Catimbau Grande, Município de Rio Bonito - Estado do Rio de Janeiro - Almeida, Domingos Corrêa de (1996)
In one year of research in Catimbau-Grande, Municipality of Rio Bonito, Rio de Janeiro State, the sandfly fauna was studied. Night catches using light traps and human bait were performed either in peridomestic and extradomestic environments. The richness of species found in each type of collection was estimated. Five species of the Lutzomyia genus were found: Lu. (Nyssomyia) intermedia, Lu. migonei, Lu. (Pintomyia) fischeri, Lu. (Lutzomyia) longipalpis and Lu. (Micropygomyia) schereiberi. Lu. intermedia was the most adapted specie between different levels of antropic action in the studied area. The presence of Lu. intermedia and Lu. migonei in peridomestic area showed the risk of leishmaniasis transmission, since, these species are suspect vectors of the disease in others brazilian regions. Lu. intermedia was more abundant and more antropophilic among captured species. In spite of the small number of species it was possible to elaborate a key based on the location and intensity of pigmentation of the thoracic region to separated the local species.